Nickel-catalyzed enantioselective domino Heck/Sonogashira coupling for construction of C(sp)-C(sp3) bond-substituted quaternary carbon centers - Hui Chen; Zhenkang Ai; Lin Guo; Licheng Yao; Yaopeng Li; Buming Gu; Yixuan Zhang; Yahu A. Liu; Boxue Tian; Xuebin Liao (Tetrahedron Chem, 2022)
Enantioselective chemical transformations to introduce sp carbons and trifluoromethyl group into 3,3-disubstituted-2-oxindoles is among chemists' most wanted. We report a single nickel-catalyzed enantioselective domino Heck/Sonogashira annulation/alkynylation process to construct an all-carbon C(sp)-C(sp3) bond-substituted or C(sp)-C(sp3) bond- and trifluoromethyl-disubstituted quaternary center at the C3 position of 2-oxindole, resulting in corresponding 3,3-disubstituted-2-oxindole in high yield with excellent enantioselectivity. Of note, we have isolated and characterized structurally a resting state intermediate, a diphosphorus complex of nickel, (dppp)NiII(alkyl)I, which provided a crucial evidence to support the mechanistic postulation and guided DFT calculations.The bigger picture: Alkynes are important structural motifs in a wide range of natural products and bioactive compounds, as well as synthetic versatility and broad applications in bio-orthogonal labelling, pharmaceuticals, and material science. Although alkynylation using transition metal has historically been accomplished, these processes are restricted to palladium, iridium, and copper catalysis. We report novel single nickel-catalyzed enantioselective domino Heck/Sonogashira coupling for construction of C(sp)-C(sp3) bond-substituted or C(sp)-C(sp3) bond- and trifluoromethyl-disubstituted quaternary carbon centers. Experimental studies, including isolation of organonickel complex combining DFT calculations demonstrate reaction pathway. This single nickel catalyzed asymmetric annulation/couplings of terminal alkynes method also provided a complementary to noble metal catalysis. Furthermore, this strategy is expected to inspire future blooming works on alkynes’ transformation by single nickel catalysis.